Characterization and Morphological Analysis of Trio-Glacial Lakes (Sankha Lake, Kukur Lake, and Thakur Jyu Lake) of Barekot Patan, Jajarkot, Nepal - Rawat, Ganesh; Khanal, Nabraj; Adhikari, Pitri Bhakta (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
Glacial lakes are essential elements of alpine ecosystems, with important functions in the hydrology and ecology of the area. However, the rapid retreat of glaciers due to climate change has led to the formation and expansion of glacial lakes, increasing the risk of glacial lake outburst floods (GLOFs) and other associated hazards. Sankha, Kukur, and Thakur Jyu, the three glacier lakes in Barekot Patan, Jajarkot, Nepal, have not yet been the subject of any scientific studies. The main objectives of this research are to provide an overview and analyze three glacial lakes in the Barekot Patan area of Jajarkot, Nepal, from a morphological perspective. Both primary and secondary sources of information were gathered. The collected data were analyzed by applying suitable statistical and GIS tools. Through field surveys, remote sensing, and GIS analysis, the study put contrast to understand the current state and potential risks associated with these lakes. The study has covered and concluded the overview of morphological characteristics, including the shape, size, and characteristics of these lakes, as well as evaluated precipitation patterns in the study area. From the study, the shape of three glacial lakes has been calculated, and from different qualitative and quantitative analyses of data, the lakes are found to be high-altitude glacial lakes. This study has offered critical insights into glacial lake dynamics in Barekot Patan, aiding sustainable development and disaster risk reduction decisions. It will empower policymakers, researchers, and communities to craft effective strategies for mitigating GLOF impacts and ensuring regional safety and sustainability. The dissemination work includes academic publications, workshops, and engagement with local communities, governmental bodies, and non-governmental organizations.